HYBRIDITY IN MODERN NIGERIAN MUSIC - Obijiaku, Chidi (International Library of African Music, 2023)
Igbo choral art music is a Nigerian genre that exhibits interesting musical hybridity as it combines a notated choral part with an un-notated orchestral part into a final musical artwork. The notated choral part is produced by the composer through a synthesis of Igbo traditional music and European classical music, while the orchestral part, based on Igbo traditional music practices, is produced by the choral director. For over five decades scholarly discussions on Igbo choral art music have focused on the notated choral part and how composers blend European classical music and Igbo traditional music principles. Although the choral part is significant, my more than two decades of participation in the genre as well as interviews with leading practitioners reveal that without the orchestral part, a composition is considered incomplete by both the practitioners and the audience. Such a critical aspect of the genre has received little to no academic attention. This article is an autoethnographic report on the orchestration principles of Igbo choral art music, its relationship with Igbo traditional music, and how such orchestration contributes to hybridity as a fundamental resource in the genre’s development.
Keywords: Igbo (African people); Oral tradition; Choral music; Composition (Music); Art; Artwork; Igbo Choral Music; Orchestration; Traditional Music; Nigeria; Musical Hybridity; African Music